Mai i Te Ao Kōhatu: Weaving - An Art Form Derive from Mātauranga Māori as a Gift from the Ancestors - Te Kanawa, Kahutoi (Te Kaharoa, 2008)
Aspects of traditional Maori weaving are examined in this article, with a focus on traditional processes of knowledge transmission, some of the practical and conceptual elements of traditional weaving and the distinction between weaving as an art as opposed to a craft.